PELAYANAN ASURANSI JIWA SYARIAH: SUDAHKAH SESUAI HARAPAN? - Ahmad Tibrizi Soni Wicaksono; Rio Trisasmita (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2018)
This study aims to analyze Gap on Islamic Life Insurance Services in DKI Jakarta by CARTER approach (Compliance, Assurance, Responsiveness, Tangibles, Empahty, Reliability), respondents in this study amounted to 150 respondents, using Cluster sampling method, this researcher use Importance Performance Analysis Method. The result of the research shows that the level of satisfaction between perception and expectation toward service to customers of Islamic Life Insurance in DKI Jakarta has a value of 97.22%, it indicates that there are still Gap on services provided by Islamic Life Insurance Company in DKI Jakarta especially on Hospitality employees in serving the customer, Ability to respond to problems arising, Ability to communicate with customers, Capacity quickly responsive to customer complaints, Use of equipment and technology in operational activities, and Application of Information technology.